Colorectal Cancer Survivors Suffering From Sensory Chemotherapy-Induced Peripheral Neuropathy Are Not a Homogenous Group: Secondary Analysis of Patients’ Profiles With Oxaliplatin-Induced Peripheral Neuropathy - Nicolas Kerckhove; Nicolas Kerckhove; Nicolas Kerckhove; Marie Selvy; Céline Lambert; Coralie Gonneau; Gabrielle Feydel; Caroline Pétorin; Agnès Vimal-Baguet; Sergey Melnikov; Sharif Kullab; Mohamed Hebbar; et al. (Frontiers in Pharmacology, 2021)
Oxaliplatin, a pivotal drug in the management of colorectal cancer, causes chemotherapy-induced peripheral neuropathy (CIPN) in a third of cancer survivors. Based on a previous cross-sectional study assessing oxaliplatin-related sensory CIPN in colorectal cancer survivors, a secondary analysis was designed to explore the possibility that different clusters of patients may co-exist among a cohort of patients with oxaliplatin-related CIPN. Other objectives were to characterize these clusters considering CIPN severity, anxiety, depression, health-related quality of life (HRQOL), patients’ characteristics and oxaliplatin treatments. Among the 96 patients analyzed, three clusters were identified (cluster 1: 52, cluster 2: 34, and cluster 3: 10 patients). Clusters were significantly different according to CIPN severity and the proportion of neuropathic pain (cluster 1: low, cluster 2: intermediate, and cluster 3: high). Anxiety, depressive disorders and HRQOL alteration were lower in cluster 1 in comparison to clusters 2 and 3, but not different between clusters 2 and 3. This study underlines that patients with CIPN are not a homogenous group, and that CIPN severity is associated with psychological distress and a decline of HRQOL. Further studies are needed to explore the relation between clusters and CIPN management.